The Effect of Prenatal Yoga on Stress Reduction in Pregnant Women - Katon Galih Wicaksono; Safira Medya Rusdamayanti; Arzeti Felyanti; Tsabitah Ayu Nismara; Maria Eno Rahayu Wibawaningrum; Djenar Ayu Hanifah; Dini Nur Alpiah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pregnancy is one of the most important stages in a woman's life, accompanied by various physiological, psychological, and social changes. This period not only affects the mother's health but also plays a crucial role in the growth and development of the fetus. To adapt to these changes, a holistic approach is needed to support the physical and mental health of pregnant women. One form of non-pharmacological intervention that is increasingly gaining popularity is prenatal yoga. Prenatal yoga is an adaptation of classical yoga tailored to the physical condition of pregnant women, with movements performed in a gentler and slower manner. The core principle of prenatal yoga is the application of breathing techniques performed with full awareness. Prenatal yoga exercises are known to improve the health of pregnant women. This study aims to examine the effects of prenatal yoga on reducing stress levels in pregnant women through an analysis of relevant literature. The results indicate that prenatal yoga is effective in reducing stress levels, improving posture, and providing relaxation benefits for the mental health of pregnant womenPrenatal Yoga